Pengaruh Public Service Motivation terhadap Organizational Citizenship Behavior: Peran Moderasi Service Climate - Dimas Prafi Al Mauludin; Reza Lidia Sari (Jurnal Psikologi Perseptual)
This study aims to analyse the effect of public service motivation (PSM) on organizational citizenship behaviour (OCB) and the moderating role of service climate in the relationship between the two variables in the context of the State Civil Apparatus in Indonesia. This research uses a cross-sectional study approach with a survey method and involves 105 state civil apparatus employees in East Java Province who serve for at least one year. The sample was drawn using accidental sampling technique. Participants completed an online questionnaire to measure the three research variables. PSM was measured with Public Service Motivation Scale (α:.81), service climate was measured with Service Climate Scale (α:.89), and OCB was measured OCB Scale (α:.94). The data analysis process in this study used moderated regression analysis techniques to test the research hypothesis. The results of this study indicate that public service motivation has a significant positive effect on organizational citizenship behavior, and service climate shows a significant positive moderating role in strengthening the relationship between public service motivation and organizational citizenship behavior.